Fintech Optimization and Digital Financial Literacy in UMKM Empowerment: A Community Service Study for Financial Inclusion in the Society 5.0 Era. - Hikmah Sekarningtyas; Suryati Eko Putro; Bincar Nasution; Rahmah Juliani Siregar; Lukmanul Hakim Aziz (PT Inovasi Pratama Internasional, 2026)
Micro, Small, and Medium Enterprises (UMKM) play a crucial role in Indonesia’s economy, contributing 61.9% to GDP and 97% to national employment. However, their digital transformation is hindered by low fintech adoption and limited digital financial literacy. This study evaluates a community service program aimed at enhancing fintech utilization and digital financial literacy among UMKM in five regencies of East Java. Using a quasi-experimental pretest-posttest control group design, 240 participants were randomly assigned to intervention and control groups. Data were collected through validated questionnaires measuring fintech adoption index (FAI), digital financial literacy index (DFLI), and business performance. The results show significant improvements in fintech adoption (21.4%, p < 0.001), digital financial literacy (18.7%, p < 0.001), and monthly revenue (17.3%, p < 0.01). These findings indicate that structured training integrating fintech and digital literacy effectively supports UMKM digital transformation and advances financial inclusion in the Society 5.0 era.